THE CORRELATION STUDY OF STREET CONFIGURATION TO THE CRIME RATES IN REDUCING URBAN CRIMES (Case Study: Sukasari, Bandung) - ARYUNDA (NIM: 25611010), HANNY
Crime has always been a social problem occurred in many part of the city including residential areas. The fear of crime continues to increase as the crime rates heightened, which eventually affects the quality of life of the residents living in the area. Residents thus resorted to provide security through relying on different kinds of strategies such as installing CCTVs and hiring security guards instead of having their neighborhood ‟naturally‟ surveillanced. However, the application is not exactly optimal, in cost and even in social life. Some strategies used on reducing crime rates by design are then developed, such as identifying the correlation between street configuration and crime incidents and suggesting better street configuration using Space Syntax. The result will help determining which configuration is correct to be applied on the area. The first step of the research is to make the axial map of the study area, which is in Sukasari, Bandung.This step is followed by analyzing the axial map using Space Syntax to discover the value of the streets by each variable so it can then be analyzed with the crime data gathered. These variables will be further analized with regression analysis to see the correlation and the strength of the influence of the street configuration towards crime incidents in Sukasari, Bandung. The result of the research shows that street configuration (global integration) influencing the crime rates in Sukasari are global integration, connectivity, and pedestrian integration. Both global integration and pedestrian integration have negative correlation with crime. This means that the higher the street is integrated, the lower the chance of crime incidents would occur. On the other hand, the area‟s connectivity has a positive correlation with crime, showing that the higher the street is connected, the higher the chance of crime incidents would occur.